Analisis Kesehatan dan Keselamatan Kerja pada Proses Produksi Konsentrat Kopi dengan Metode Preliminary Hazard Analysis : (Studi Kasus Aroma Kahuripan) - Louisa Dhevea Kylla Putri Prasmita (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
The coffee concentrate production process is still classified as not having good K3 due to the lack of appropriate personal protective equipment and good organization. This research is a qualitative research. Primary data itself consists of production data, including production flow. Through research related to Occupational Safety and Health carried out in the Aroma Kahuripan production process, it was found that there were several risks of work accidents that could occur. The potential for work accidents in the coffee powder cooking process has a priority risk level of 1, which indicates that it requires immediate treatment. Handling potential work accidents requires an appropriate K3 system. Suggestions for reducing the potential for accidents include personal protective equipment, designing workstations and additional equipment, as well as regular checks. With this proposal, companies can reduce the potential for work accidents.